Atorvastatin Ameliorates Ischemia Reperfusion Injury in Rat Heart - Rohilla, Ankur (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTThe present study was designed to investigate the effect of Atorvastatin, a 3-hydroxymethyl-glutaryl coenzyme A (HMG-CoA) reductase inhibitor, on ischemia-reperfusion (I/R)-induced myocardial injury. The isolated Langendorff-perfused rat hearts were subjected to global ischemia for 30 min followed by reperfusion for 120 min. Myocardial infarct size was assessed by volume methods using triphenyltetrazolium chloride staining. Coronary effluent was analyzed for the release of lactate dehydrogenase (LDH) and creatine kinase (CK) to assess the degree of cardiac injury. Moreover, oxidative stress in the heart was assessed by measuring lipid peroxidation, superoxide anion generation and reduced glutathione. I/R was noted to produce myocardial injury, as assessed in terms of increase in myocardial infarct size, LDH and CK in coronary effluent. Moreover, oxidative stress was noted to be increased due to I/R injury as assessed in terms of decreased TBARS (thiobarbituric acid-reactive substance) and superoxide anion generation levels alongwith increase in reduced glutathione levels in the heart. Treatment with Atorvatstain (25 µM, 50 µM and 100 µM) afforded cardioprotection against I/R-induced myocardial injury in rat hearts as assessed in terms of reductions in myocardial infarct size, LDH and CK levels in coronary effluent. Moreover, the high degree of oxidative stress produced as a result of I/R injury was noted to be reduced by Atorvastatin treatment. It may be concluded that reductions in infarct size and oxidative stress may be responsible for the observed cardioprotective potential of Atorvastatin against I/R-induced myocardial injury.Key words: Atorvastatin, HMG-C0A, Ischemia-reperfusion injury, Oxidative stress